Pelatihan Dasar Teknik Tenaga Listrik Bagi SMA Kesatrian 2 Semarang - Nurhayati, Titik; Destyningtias, Budiani; ISYA ARYAN, ISYA ARYAN SULISTYO; Nurul, Yusuf (Gotong Royong, 2025)
The distribution system and method of installing electrical installations in Indonesia must follow the rules set by PUIL (General Regulations on Electrical Installations) which was published in 1977, then revised in 1987 and last in 2011. PUIL 2011 is the main technical reference for installing low voltage electrical installations. The purpose of this community service is to provide knowledge to students about the importance of electrical lighting installations in accordance with PUIL regulations to avoid the danger of fire or electric shock. Another goal is to provide knowledge about work safety in installing electrical installations because of the frequent occurrence of work accidents during installation. The problems faced by the community are the lack of knowledge of the community / high school students about (1) Lack of special skills for Kesatrian High School graduates in analyzing electrical problems, especially in electrical lighting installations in accordance with PUIL standards (2) Lack of detailed explanation through a theoretical approach regarding the basic problems of electrical lighting installations for graduates of SMA Kesatrian 2. The training provided is in the form of providing material explanations, regarding the basic legal understanding of electrical installations, Law No. 30 of 2009 concerning Electricity, Government Regulation (PP) No. 25 of 2023 concerning       Electrical Safety Replacing PP No. 10 of 1989 and updating safety standards,” In addition, there is ESDM Ministerial Regulation No. 12 of 2021 concerning Electrical Power Utilization Installations SNI 04-0225-2000 concerning Procedures for planning electrical installations in Buildings. The expected results are that students can read single diagram drawings and wiring diagrams, are able to apply them in practice in the field and indirectly develop a sense of independence. The approach methods offered to solve the partner's problem are (1) providing training to students of Kesatrian 2 Semarang High School about the electrical power installation process, (2) conducting simulations about how to install electrical power.